The importance of recreational public facilities within the urban space in meeting the psychologicl and social needs of the child: The case of 206 dwellings in the city of M’Sila - Feloussia, Lahcen; Hadji, Abdelkader; Matoug, Siham (Journal of Architecture and environment of child, 2021)
That interest in the psychological preparation of the child-social is important step in achieving compatibility and adaptation and this is not only the station of needs physiological, biological, social and psychological. The need to play include in the social and psychological needs; as he learns from playing social customs and spirit of cooperation, altruism, love of others and the dynamics of the group, and mental habits like love and trust and configure the right directions. It also contributes to expand the circle of his interest and make it a more disciplined in terms of behavioural, The importance of this topic lies in addressing a sensitive segment of society, namely children, who must be taken care of and given more attention and provide all their needs, especially when it comes to playing in the early childhood stage, as it seeks to raise the child healthy, sound and enhance his values It gives him self-confidence and develops his mental abilities. This is on the one hand, and on the other hand, it is to provide a safe environment for the child so that he can regularly participate in play and build social relationships. In the presence of safe spaces prepared for playing near the residential areas in which they live. The study relied on a methodology based on two levels: The first is the theoretical approach, which sheds light on some general aspirations related to children and playing spaces, while addressing the necessary conditions for creating and equipping these spaces. As for the analytical approach, it is represented mainly in the analysis of the study model - the neighbourhood of 206 dwellings in the city of M’sila, with reliance on field observation in it. This paper studies the importance of playing spaces in achieving the child’s desires in the stages of his development in which his needs differ and his view of entertainment and entertainment as a complement to his biological, physiological, emotional and social needs.